Andromonoecy in Gynandropsis gynandra (L.) Briq. (Cleomaceae) and effects on fruit and seed production - Zohoungbogbo, Herbaud P. F.; Houdégbé, Carlos A.; Sogbohossou, E. O. Dêêdi; Tossou, Monique G.; Maundu, Patrick; Schranz, Eric; Van Deynze, Allen; ZOUNDJIHEKPON, JEANNE; Achigan-Dako, Enoch Gbenato (My University, 2018)
Spider plant (Gynandropsis gynandra) is a traditional leafy vegetable widespread in sub-Saharan Africa and tropical Asia that is also valued for its medicinal properties. Developing a breeding program for the species requires detailed knowledge of its phenology, floral morphology and pollination system. This study investigates the effects of floral morphology and pollination mechanisms on the reproductive success in G. gynandra. The experiments were conducted in two locations in Benin. A split-plot design was used with four randomized complete blocks. Three accessions were randomly assigned to the whole plots and five treatments including natural self-pollination, hand self-pollination, geitonogamy, open pollination and hand cross-pollination were randomized over the sub-plots. We observed that individual plant exhibited 70% of staminate (male) flowers and 30% of hermaphrodite flowers. G. gynandra was andromonoecious. Open pollination and hand cross-pollination led to higher fruit and seed set. Natural self-pollination and hand self-pollination resulted in lower fruit and seed production. G. gynandra is a self-compatible and predominantly out-crossing species. Cross-pollination resulted in a significant increase in fruit set. This study set the ground for the development of improved cultivars in G. gynandra.
Keywords: Andromonoecy Anthesis Gynandropsis gynandra Hermaphroditism Pollination systems